PILAR: a Federation of VISIR Remote Laboratory Systems for Educational Open Activities - Garcia-Loro, Felix (2018)
Social demands have promoted an educational approach based on an “anywhere and anytime” premise. Remote laboratories have emerged as the answer to the demands of technical educational areas for adapting themselves to this scenario. The result has not only benefit distance learning students but has provided new learning scenarios both for teachers and students as well as allowing a flexible approach to experimental topics. However, as any other solution for providing practical scenarios (hands-on labs, virtual labs or simulators), remote labs face several constraints inherited from the subsystems of its deployment  hardware (real instruments, equipment and scenario) and software (analog/digital conversions, communications, workbenches, etc.). This paper describes the Erasmus+ project Platform Integration of Laboratories based on the Architecture of visiR (PILAR) which deals with several units of the federation installed in different educational institutions and devoted to analog electronics and electrical circuits. Based on the limitations of remote labs, the need for the federation will be justified and its benefits will be described by taking advantage of its strengths. The challenges that have come up during the different stages and the different approaches to design are also going to be described and analyzed